Localization of 5-methylcytosine in metaphase chromosomes of diploid and triploid pacu fish, Piaractus mesopotamicus (Pisces, Characiformes) - de Almeida-Toledo, L. F.; Viegas-Pequignot, E.; Coutinho-Barbosa, A. C.; Foresti, F.; Niveleau, A.; Toledo-Filho, S. D. (Karger, 1998)
The distribution of 5-methylcytosine (5-MeC) was investigated in fish chromosomes by indirect immunofluorescence using a highly specific 5-MeC monoclonal antibody. Diploid and artificially produced triploid specimens of the pacu fish, Piaractus mesopotamicus, were analyzed. The strong immunofluorescent signals were coincident with the heterochromatic regions of both diploids and triploids in a pattern that matched the C-banding pattern. In the euchromatin, heterogeneous labeling was observed along the chromatids. The weakness of this labeling hindered comparison of the fluorescence labeling of homologous chromosomes from diploid and triploid individuals. However, no striking differences were observed. The possibility that the euchromatin labeling by the 5-MeC antibody is related to the occurrence of mildly repetitive sequences in the genome of Piaractus is discussed.